A longitudinal vortex wind turbine: Numerical study. Issue 180 (September 2018) - Hemsuwan, Withun; Sakamoto, Kasumi; Nakada, Shota; Takahashi, Tsutomu
Abstract: The longitudinal vortex wind turbine (LV-WT) is a new windmill concept which uses circular cylinders as the turbine blades and not Magnus rotors. The driving force is produced by the longitudinal vortex (LV). A ring-shaped plate is installed behind the circular blades for employing the LV. In this study, the aerodynamic mechanism of the LV-WT system is numerically investigated using the unsteady Reynolds-averaged Navier-Stokes (URANS) simulation. A small model of the two blades is evaluated in a wind tunnel for comparison with the CFD results. The computational and experimental predictions correlate very well with only a small difference. The numerical visualizations show the vortical structure near the crossing includes the necklace vortex (NV) and the trailing vortices (TVs). The driving force (lift) is produced due to the longitudinal vortex induced suction-flow in the leading region. The distributions of the aerodynamic force coefficients are continuously evaluated along the blade length in order to examine the 3D effects of the LV, and visualizing the flow fields around the system is employed to discuss the aerodynamic reasons. Cross-flow over a stationary isolated-cylinder is also simulated to compare the mechanism by visualizing the limiting streamlines on the cylinder surface. Highlights: CFD results were validated with experimental data of the wind tunnel test. Three-dimensional structure of the longitudinal vortex was visualized. The limiting streamlines showed the flow pattern on the cylinder surface. Distributions of the aerodynamic forces were continuously investigated along the blade length.